Investigating the Relationship Between Islamic Work Ethics and Organizational Commitment and related factors in the Employees of Guilan University of Medical Sciences - Mitra Abolhasanpour Chelaras1; Morteza Rahbar Taramsari2; Maryam Ghalandari; Habib Eslami Kenarsari4 Eslami Kenarsari4 (مجله دانشگاه علوم پزشکی گیلان, 2025)
Background: Much of the actions and behaviors of employees and managers within organizations are influenced by moral values and have roots in ethics. Disregarding work ethics in organizational management can lead to significant challenges for organizations and question the legitimacy of the organization and its actions. Objective: Therefore, this study aimed to explore the relationship between Islamic work ethics and organizational commitment among employees of Guilan University of Medical Sciences during the years 2021-2022. Methods: This study was conducted in an analytical cross-sectional manner over a 6-month period. A total of 353 employees working in the deputyships of the Guilan University of Medical Sciences were selected through stratified proportional sampling and studied. The tools used for data collection were Ali and Al-Kazemi's 1988 Islamic Work Ethics Questionnaire and Allen and Mayer's Organizational Commitment and Job Satisfaction. Results: A statistically positive and significant relationship was observed between the organizational commitment variables and each of its dimensions with work ethics (P-value < 0.001). This relationship was stronger between affective commitment and Islamic work ethics, with a correlation coefficient of 0.402, while the relationship between continuous commitment and Islamic work ethics was weaker, with a coefficient of 0.164 (P-value < 0.001). Conclusion: The findings of this research conducted among employees of Guilan University of Medical Sciences indicated a positive relationship between Islamic work ethics and the dimensions of organizational commitment. The high scores of employees in the job satisfaction and Islamic ethics indicate that employees, while experiencing job satisfaction, adhere to the principles of Islamic work ethics.